Development Of Medicine in Central Asian Kingdoms - Oydinoy Ochilova (Zien Journals, 2024)
During the years of independence of Uzbekistan, in a number of regions, representatives of traditional medicine stood side by side with health workers and took an active part in measures to protect public health. Actively participating in public health activities, along with doctors enjoying great reputation and attention among the population, the number of “fake” doctors has also increased.
Keywords: Medicine; hospital; doctors; pharmacology